2008
DOI: 10.1128/jb.00655-08
|View full text |Cite
|
Sign up to set email alerts
|

NorB, an Efflux Pump in Staphylococcus aureus Strain MW2, Contributes to Bacterial Fitness in Abscesses

Abstract: While remaining a major problem in hospitals, Staphylococcus aureus is now spreading in communities. Strain MW2 (USA400 lineage) and other community methicillin-resistant S. aureus strains most commonly cause skin infections with abscess formation. Multidrug resistance (MDR) efflux pumps contribute to antimicrobial resistance but may also contribute to bacterial survival by removal of environmental toxins. In S. aureus, NorA, NorB, NorC, and Tet38 are chromosomally encoded efflux pumps whose overexpression can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 31 publications
(25 reference statements)
1
102
0
Order By: Relevance
“…Perhaps more likely is the possibility that low pH serves as a signal to the bacterial cell of its presence in an environment in which increased expression of NorB is beneficial for other reasons. One such notable example is a bacterial abscess in which low pH may be a signal for the increased expression of norB that we have shown occurs in this environment (8). Although its natural substrate in an abscess environment remains unknown, NorB has been shown to contribute selectively to bacterial survival in this common type of S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps more likely is the possibility that low pH serves as a signal to the bacterial cell of its presence in an environment in which increased expression of NorB is beneficial for other reasons. One such notable example is a bacterial abscess in which low pH may be a signal for the increased expression of norB that we have shown occurs in this environment (8). Although its natural substrate in an abscess environment remains unknown, NorB has been shown to contribute selectively to bacterial survival in this common type of S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of norB, encoding the NorB efflux pump, causes reduced susceptibility to moxifloxacin in vitro and contributes to bacterial fitness in a subcutaneous abscess model (8). Since norB expression was increased shortly after a shift to pH 4.5, we wished to determine whether susceptibility to moxifloxacin, a NorB substrate (24), was also affected by a shift to pH 4.5.…”
Section: Effect Of Acid Ph On Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Balb/C mice (Harlan) were immunized as described above. An s.c. skin/skin structure abscess model was implemented for these studies as modified from Voyich et al (84) and Ding et al (85). In brief, on study day 35, mice were anesthetized, their flanks were shaved and sterilized, and the mice were randomized into appropriate study groups.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that increased resistance to antibiotics, biocides and dyes has been associated with NorA and NorB mediated efflux pumps (Handzlik et al, 2013;Sabatini et al, 2012;Truong-Bolduc et al, 2005;Ding et al, 2008). However, antimicrobial resistance associated with NorA and NorB efflux pumps is poorly characterized in S. aureus (Handzlik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%